PENGARUH PEMBERIAN PROPRIOCEPTIVE NEUROMUSCULAR FACILITATION (PNF) TERHADAP PENINGKATAN FUNGSIONAL UPPER LIMB PADA PASIEN PASCA STROKE - Indra Sylva Mahmudi; Heru Purbo Kuntono; Aditya Johan Romadhon (Jurnal Nasional Fisioterapi, 2023)
Background: Stroke is a major health problem that can cause disability and even death in adults and the elderly. The problems of post-stroke patients is the decreased ability to control the upper limbs which can result in decreased functional abilities. Decreased functional ability of the upper limbs can be treated wtih proprioceptive neuromuscular facilitation. Objective: to determine the effect of PNF on increasing the functional ability of the upper limbs in post-stroke patients. Method: this study used a randomized pre- and post-test design with control. Subjects that suitable with inclusion crtiteria totaled 17 people and were divided into 2 Groups. Group 1 consisted of 9 subject were given PNF. Group 2 as control consisted of 8 subject given routine hospital therapy. Measurement of functional ability using FMA-UE at the beginning and end of treatment. Results: The results of statistical tests before and after treatment Group 1 obtained a value of p = 0.000 (p <0.05). The results of the hypothesis test after treatment in Group 2 yielded p = 0.038 (p <0.05) and the results of the tests between groups p = 0.000 (p <0.05) Conclusion: Giving PNF intervention in Group 1 has a better effect than Group 2.